Remonstrance against Decisions Made by Central Administrative Bodies in the Czech Republic - Soňa Skulová; Lukáš Potěšil; David Hejč (Central European Public Administration Review)
The remonstrance is traditional standard (ordinary) remedial measure which can be (only) applied after the first instance decision has been issued by central administrative body. The article is heading to verify the hypothesis whether the remonstrance does reflect the principle of two instances in entirety. As the finding of the research it can be pointed out that the remonstrance represents relative exclusion of the principle of two instances, which is applied only in a modified form, as the remonstrance is not decided by any higher, independent administrative authority, but by the identical central administrative body, namely by its head, not by its remonstrance committee, which issues „only“ recommendations/advices. We concluded that possible solutions are either transformation remonstrance committees into administrative bodies/tribunals, or rules providing the central administrative bodies do not make first instance decisions.